Physical activity and sedentary behaviour typologies of 10-11 year olds - Brockman Rowan; Page Angie S; Fox Kenneth R; Jago Russell; Thompson Janice L (BMC, 2010)
Abstract Background Targeted interventions may be more effective at increasing children's physical activity. The aim of this study was to identify clusters of children based on physical activity and sedentary patterns across the week. Methods Participants were 761, 10-11 year old children. Participant's self-reported time spent in eight physical activity and sedentary contexts and wore an accelerometer. Cluster analysis was conducted on the time spent in the self-reported physical activity and sedentary contexts. Mean minutes of accelerometer derived of moderate to vigorous physical activity (MVPA) and sedentary time were derived for the entire week, weekdays only, weekend days and four different time periods across each type (weekend or weekday) of days. Differences in the physical activity patterns of the groups derived from the cluster analysis were assessed for overall physical activity as well as for the four time periods on weekdays and weekend days. Results Three clusters emerged: 1) High active/Low sedentary; 2) Low active/Moderate sedentary; and 3) High Active/High sedentary. Patterns of activity differed across the week for each group and the High Active/High sedentary obtained the most minutes of MVPA. Conclusions Patterns of physical activity and sedentary time differed across the week for each cluster. Interventions could be targeted to the key periods when each group is inactive.